Quality of life assessment in patients after laparoscopic cholecystectomy - Starodub , Tetiana; Bogomaz, Volodymyr (The Ukrainian Scientific Medical Youth Journal, 2025)
Laparoscopic cholecystectomy is widely recognized as the gold standard for surgical treatment of gallstone disease. Despite its high efficacy and low rate of early complications after surgery, some patients still experience abdominal symptoms after surgery. The results of some studies show that approximately 25% of patients experience abdominal complaints requiring medical assessment one month after surgery. Active postoperative follow-up is considered to play a key role in improving patients' quality of life and identifying symptoms that remain after surgery for various reasons. With the growth of digitalization in health care, telemedicine technologies are opening up new opportunities to improve the effectiveness of postoperative monitoring. However, telemedicine services also face a number of challenges, including technical limitations, unequal access to digital technologies, the need to adapt clinical protocols, and the potential threat to patient data security. The present prospective study was conducted between 2024 and 2025 at two medical institutions in Ukraine. The study comprised 70 patients who underwent laparoscopic cholecystectomy for gallstone disease. The age of participants ranged from 24 to 67 years, with a mean age of 44.3 ± 10.8 years. Exclusion criteria included performing open instead of laparoscopic cholecystectomy, complicated intraoperative course, severe comorbidities (decompensated diabetes mellitus, malignancies, advanced heart failure), psychiatric disorders, lack of internet access, or refusal to participate in telemedicine follow-up. The patients were divided into two groups: the main group received postoperative support using telemedicine, while the control group received traditional outpatient care. Patients in the main group were at liberty to seek face-to-face outpatient care at any time. Quality of life was assessed using validated Ukrainian versions of the EQ-5D-5L and SF-36 questionnaires 1, 6, and 12 months after surgery. The results showed positive changes in quality of life for the entire group during the year after the intervention. The average EQ-5D-5L index increased from 0.90 to 0.95 over 11 months, and the physical and psycho-emotional components of the SF-36 increased from 70.3 to 82.6 and from 73.0 to 85.0, respectively. It is worth noting that at no stage of the observation were there any statistically significant differences between the main and control groups in terms of quality of life as assessed by the above-mentioned questionnaires. This finding indicates that telemedicine tools may be as effective as traditional postoperative supervision in terms of quality of life. The introduction of telemedicine into postoperative care is safe, effective and patient-centered, especially in cases where in-person consultations are not possible or require additional financial or time costs. The study suggests that telemedicine could be a valuable option of postoperative management for patients who have undergone laparoscopic cholecystectomy, highlighting its potential for wider integration into routine postoperative management.